Development Trends in Regional Railway Vehicles (Current Problems in Rail Vehicles, 2021)
Stimulation of transport demand by quality of transport supply, environmental aspects and economic efficiency of regional passenger railway transport. High cruising speed as an indicator of the quality of regional transport and as a necessary condition for the running of regional trains in parallel with long-distance passenger trains as well as fast freight trains on heavily used railway main lines. Traction and braking parameters of EMU as a tool to increase cruising speed. Energy management of regional trains. Management of reducing the specific weight of vehicles for regional passenger transport.
Keywords: regional trains; efficiency; speed; comfort